The Emerging Indigenous Language Economy: Labour Market Demand for Indigenous Language Skills in the Upper Great Lakes - Meades, Sean; Pine, Deb; Broad, Gayle (Journal of Aboriginal Economic Development)

(untitled) (Captus Press, 2019)
Language revitalization is necessarily intertwined with economic spheres, as Grenoble and Whaley have expressed that the economic wellbeing of a community influences its ability to engage in such efforts (2006, p. 44). Conversely, health researchers assert that cultural continuity, in which language is inextricably linked, is a prerequisite to self-sufficiency and community sustainability (Oster, Grier, Lightning, Mayan, & Troth, 2014). Nonetheless, the place of Indigenous language(s) within labour market research has often focused on the need for greater access to dominant-language education (MacIsaac & Patrinos, 1995) or the impact on wage differentials (Chiswick, Patrinos, & Hurst, 2000) while research on Indigenous language revitalization in Canada has been largely silent on the relationship to economic spheres, and community economic development literature has engaged with notions of culture more broadly. Drawing on interviews and focus groups from a selection of Anishinaabe communities in Northern Ontario, Canada, this research identifies existing needs for Anishinaabe language speakers within the regional labour market, showcasing the oft-overlooked economic demand for Indigenous language skills. Support for this project was provided by the Ontario Human Capital Research and Innovation Fund from the Ministry of Training, Colleges and Universities.